Recurrent Disease After Esophageal Cancer Surgery: A Substudy of The Dutch Nationwide Ivory Study. Issue 5 (26th November 2022) - Kalff, Marianne C.; Henckens, Sofie P.G.; Voeten, Daan M.; Heineman, David J.; Hulshof, Maarten C.C.M.; van Laarhoven, Hanneke W.M.; Eshuis, Wietse J.; Baas, Peter C.; Bahadoer, Renu R.; Belt, Eric J.T.; Brattinga, Baukje; Claassen, Linda; et al.
Abstract : Objective: This study investigated the patterns, predictors, and survival of recurrent disease following esophageal cancer surgery. Background: Survival of recurrent esophageal cancer is usually poor, with limited prospects of remission. Methods: This nationwide cohort study included patients with distal esophageal and gastroesophageal junction adenocarcinoma and squamous cell carcinoma after curatively intended esophagectomy in 2007 to 2016 (follow-up until January 2020). Patients with distant metastases detected during surgery were excluded. Univariable and multivariable logistic regression were used to identify predictors of recurrent disease. Multivariable Cox regression was used to determine the association of recurrence site and treatment intent with postrecurrence survival. Results: Among 4626 patients, 45.1% developed recurrent disease a median of 11 months postoperative, of whom most had solely distant metastases (59.8%). Disease recurrences were most frequently hepatic (26.2%) or pulmonary (25.1%). Factors significantly associated with disease recurrence included young age (≤65 y), male sex, adenocarcinoma, open surgery, transthoracic esophagectomy, nonradical resection, higher T-stage, and tumor positive lymph nodes. Overall, median postrecurrence survival was 4 months [95% confidence interval (95% CI): 3.6–4.4]. After curatively intended recurrence treatment, median survival was 20 months (95% CI: 16.4–23.7). Survival was more favorable after locoregional compared with distant recurrence (hazard ratio: 0.74, 95% CI: 0.65–0.84). Conclusions: This study provides important prognostic information assisting in the surveillance and counseling of patients after curatively intended esophageal cancer surgery. Nearly half the patients developed recurrent disease, with limited prospects of survival. The risk of recurrence was higher in patients with a higher tumor stage, nonradical resection and positive lymph node harvest.